Vocational Guidance in Lithuanian General Education Schools: Achievements and Aspects to Be Improved - Žibeniene, Gintaute; Virbalienė, Rita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This paper summarizes the achievements and aspects to be improved in vocational guidance in Lithuanian general education schools in order to stimulate discussion about the experience in vocational guidance. The object of the research is an analysis of achievements and challenges in vocational guidance in Lithuanian general education schools. The aim of the research is to present and summarize the results of the analysis. The results suggest that Lithuania has managed to develop a vocational guidance system with infrastructure and monitoring. However, further development of the system of vocational guidance is hindered by changes of vocational guidance priorities, ongoing discussions about the concepts of vocational guidance and its definition as well as their interpretation within the system, lack of professional research, absence of systemic evaluation of the competence of the authorities that coordinate vocational guidance, difference in the experience of specialists and structural units in collaboration with scientists, when such cooperation is poor or even non-existent.